2007
DOI: 10.1007/s11172-007-0343-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 3-cyclopropyl-3-oxopropionitrile anion generated by electroreduction of 5-cyclopropylisoxazole

Abstract: 3 Cyclopropyl 3 oxopropionitrile anion obtained by cathodic reduction of 5 cyclopropyl isoxazole in an aprotic medium was used as an example to demonstrate that cyano ketone anions show a dual reactivity. The reaction of acetyl chloride with the electrogenerated tetrabutylammonium salt of 3 cyclopropyl 3 oxopropionitrile gave O acylation products, whereas the reaction with its sodium salt gives C acylation products. The reactions of these salts with hydroxylamine hydrochloride follow a different route: in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[313] Petrosyan et al carried out condensation of 5-aminoisoxazole 590 with 4,4,4-trifluoro-1-(2-thienyl)butane-1,3-dione 1 in acetic acid to form isoxazolo [5,4-b]pyridine 591 regioselectively (Scheme 208). [314] Kotljarov et al reported the synthesis of polyfluoroalkylcontaining fused pyridines 594-596 and chromanones 593 by treating 3-(polyfluoroacyl)-4H-chromen-4-ones 80 with aminoheterocycles 592 (Scheme 209). [315] Authors mentioned that the ratio of the products is dependent on the structure of aminoheterocycle, and solvent employed.…”
Section: Other Fused and Bridgehead Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…[313] Petrosyan et al carried out condensation of 5-aminoisoxazole 590 with 4,4,4-trifluoro-1-(2-thienyl)butane-1,3-dione 1 in acetic acid to form isoxazolo [5,4-b]pyridine 591 regioselectively (Scheme 208). [314] Kotljarov et al reported the synthesis of polyfluoroalkylcontaining fused pyridines 594-596 and chromanones 593 by treating 3-(polyfluoroacyl)-4H-chromen-4-ones 80 with aminoheterocycles 592 (Scheme 209). [315] Authors mentioned that the ratio of the products is dependent on the structure of aminoheterocycle, and solvent employed.…”
Section: Other Fused and Bridgehead Heterocyclesmentioning
confidence: 99%
“…carried out condensation of 5‐aminoisoxazole 590 with 4,4,4‐trifluoro‐1‐(2‐thienyl)butane‐1,3‐dione 1 in acetic acid to form isoxazolo[5,4‐ b ]pyridine 591 regioselectively (Scheme 208). [314] …”
Section: Trifluoromethyl‐β‐dicarbonyls Based Synthesis Of Heterocyclesmentioning
confidence: 99%